Between appropriation and occupation: the spatial politics of ‘squatting’ in East Berlin - Vasudevan, A (Routledge, 2019)
At the heart of this paper is a detailed reconstruction of the relatively unknown history of illegal occupation in East Berlin otherwise known as Schwarzwohnen. Schwarzwohnen was not a marginal phenomenon but involved thousands of citizens in the 1970s and 1980s in East Berlin and other major cities including Halle, Dresden, Leipzig, Potsdam, Erfurt and Jena. The paper follows the everyday practices adopted by so-called squatters in East Berlin. It places particular emphasis on the relationship between Schwarzwohnen and the articulation of alternative forms of dwelling and occupation that challenged official state priorities. To do so, it argues that the rise of Schwarzwohnen was part of a growing body of informal practices used by citizens in the GDR in response to housing insecurity and scarcity. These were efforts that highlighted the various ways in which citizens took control of their own housing needs outside the official housing system. They also anticipated the development of the oppositional cultures and infrastructures that erupted in the Eastern half of the city in the winter of 1989. At stake here, is an approach to housing insecurity that challenges our understanding of the socialist city and its (largely) peripheral place within urban theory.